1996
DOI: 10.1590/s0034-89101996000300002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal neurotic symptoms and infants' risk of developing persistent diarrhoea

Abstract: A previously calculated predictive model for health risk selects infants who suffer 4-5 times more morbidity than their unselected peers. Preliminary results suggested that this risk is related to maternal neurotic symptomatology. To evaluate this hypothesis, 52 consecutive mothers whose infants had a positive predictive score (Group 1) and 52 in whom this was negative (Group 2) were evaluated by means of Goldberg's General Health Questionnaire (GHQ -30). A total of 41.9% and 20.5% of the mothers in Groups 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This paper extends the growing body of literature from Pakistan, Chile and Nigeria linking poor maternal mental health to increased risk of infant illness 18 22 23. In this study, persistent perinatal CMD symptoms were associated with more than double the risk of an infant diarrhoeal episode during the first 2 months of life.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This paper extends the growing body of literature from Pakistan, Chile and Nigeria linking poor maternal mental health to increased risk of infant illness 18 22 23. In this study, persistent perinatal CMD symptoms were associated with more than double the risk of an infant diarrhoeal episode during the first 2 months of life.…”
Section: Discussionsupporting
confidence: 69%
“…In Pakistan,23 infants of mothers with postnatal depression had 2.3 times the odds of having five or more diarrhoeal episodes in their first year, after adjusting for confounders. Studies from Chile22 and Nigeria18 found similar associations with infant diarrhoeal episodes and other illnesses, although neither study adjusted for confounders. Possible mechanisms underlying the association have been postulated24 although not investigated systematically.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, only few studies examined the association between maternal mental health and child illness [5, 18, 19]. Nguyen et al discovers association of maternal mental health with both diarrhea and ARI [5].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found similar associations with episodes of diarrhea and other childhood diseases in Nigeria, but none of them were adjusted for confounding factors. 20 Possible mechanisms underlying these associations have been postulated, but not systematically investigated.…”
Section: Positive Resultsmentioning
confidence: 99%